367 TOWARDS PERSONALIZED INDUCTION THERAPY FOR ESOPHAGEAL ADENOCARCINOMA: ORGANOIDS DERIVED FROM ENDOSCOPIC BIOPSY RECAPITULATE THE PRE-TREATMENT TUMOR. (14th September 2020) - Derouet, M; Allen, J; Wilson, G; Ng, C; Radulovich, N; Kalimuthu, S; Tsao, M; Darling, G; Yeung, J
Abstract: : Esophageal adenocarcinoma has few known recurrent mutations and therefore robust, reliable and reproducible patient-specific models are needed for personalized treatment. Patient-derived organoid culture is a strategy that may allow for the personalized study of esophageal adenocarcinoma and the development of personalized induction therapy. Methods: We developed a protocol to establish EAC organoids from endoscopic biopsies of treatment naïve esophageal adenocarcinomas. Organoids were then characterized using histology and whole exome sequencing. Organoids were then exposed to clinically used chemotherapy and response assessed. Results: Our success rate for establishing the endoscopic organoid was 60%. Histologic characterization (we used p53 and cytokeratin7 as markers) and molecular characterization of organoids by whole exome sequencing demonstrated recapitulation of the tumors' histology and genomic (60% of the mutations were shared between the organoids and the endoscopic biopsies) characteristics. Drug testing using clinically appropriate chemotherapeutics and targeted therapeutics showed an overlap between the patient's tumor response and the corresponding organoids' response. Conclusion: In conclusion, organoids can be successfully cultured from endoscopic biopsies of esophageal adenocarcinoma and recapitulate the originating tumor. This model demonstrates promise as a tool to better personalize therapy for esophageal adenocarcinoma patients.